Hasil dan Komponen Hasil Galur-Galur Kedelai di Dua Lokasi - Kuswantoro, Heru; Ujianto, Lestari; Sulistyo, Apri; Hapsari, dan Ratri Tri (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTGenotype x environment interaction always presents in soybean multilocation trials in Indonesia. The objective of the research was to determine the performance of yield and yield components of soybean promising lines in two locations. A total of 11 promising lines, and three check varieties (Tanggamus, Wilis, and Anjasmoro) were evaluated in NTB and DIY in dry season 2013. The design was randomized complete block design with three replications. The results showed that yield and yield components were influenced by locations, genotypes and genotypes x locations interaction, except for days to maturity which was not influenced by the location. Number of filled pods had a significant positive correlation with grain yield of soybean. TGM/Anj-773 line had high average yield at two locations and higher than the check variety (Tanggamus).Keywords: correlation, genotype x environment, Glycine max